INTEGRATING UNIVERSAL DESIGN FOR LEARNING AND DIGITAL TECHNOLOGY: ADVANCING INCLUSIVE EDUCATION IN THE 21ST CENTURY - Mayasari, Linda Ika; Dulyapit, Apit; Yunitasari, Septiyani Endang; Syam, Aldo Redho (LP2M IAIN Sultan Amai Gorontalo, 2025)
The purpose of this article is to comprehensively examine the integration of Universal Design for Learning (UDL) principles and digital technology within the context of 21st-century inclusive education through a narrative literature review. This study employs a narrative literature review method with a qualitative and exploratory approach. The data sources consist of 15 international journal articles published between 2023 and 2025. The research instrument is a manually developed data extraction sheet used to gather information from each article. Data analysis utilizes qualitative thematic analysis with a deductive approach, referencing the UDL theoretical framework. The results of this study: (1) Teachers' knowledge and attitudes towards inclusion remain limited and inconsistent; (2) Structural and policy limitations hinder the implementation of inclusive education; (3) The role of digital technology in supporting the application of UDL to create flexible and adaptive learning; and (4) Issues of access and social justice in higher education, particularly for vulnerable groups such as refugees and individuals with disabilities. This study implies that 21st-century inclusive education cannot be separated from digital transformation and flexible learning design paradigms such as UDL. Technology is positioned not just as an assistive tool but as a structural foundation for designing learning that is responsive to diversity. Approaches based on quality of life, cultural intelligence, and recognition of the socio-political context of learners are key elements in the development of a substantively inclusive educational system.